The effects of transcutaneous auricular vagus nerve stimulation in epilepsy comorbid with migraine on the EEG power spectrum: a randomized controlled trial - Ma, Shuai; Du, Jinyuan; Luo, Cheng; Wu, Xiao; Liu, Linli; Liu, Tingting; Zhang, Xin; Yang, Lili; Liu, Jie; Luo, Yi; Zhang, Sheng; Rodriguez-Labrada, Roberto; et al. (Frontiers in Neurology, 2025)
BackgroundMigraine is a common comorbidity in patients with epilepsy, with a comorbidity rate ranging from 9.3 to 34.7%. Transcutaneous auricular vagus nerve stimulation (taVNS) is an emerging therapy used in both epilepsy and migraine treatment. However, there are currently no randomized controlled studies (RCTs) using taVNS for epilepsy complicated with migraine.ObjectiveIn this study, we evaluated the effect of taVNS as an adjuvant therapy on patients with comorbid epilepsy and migraine.MethodsForty comorbid patients (taVNS n = 20, tanVNS n = 20) were recruited and randomly grouped. The taVNS group received the true stimulus, whereas the tanVNS group received a pseudostimulus. Outcome assessment was performed at baseline and 24 weeks after initiation. We used t-test and non-parametric tests to analyse the data.ResultsThe frequencies of migraine attacks and seizures significantly decreased in the taVNS group from baseline to 24 weeks (migraine attack frequency, p = 0.002; seizure frequency, p = 0.004), and so did in Self-Rating Anxiety Scale (SAS) score (p < 0.001) and Self-Rating Depression Scale (SDS) score (p < 0.001). The QOLIE-31 scores increased after 24 weeks of taVNS treatment (p = 0.028). Moreover, taVNS reduced the EEG power spectrum in four frequency bands at 16 electrode locations in comparison between groups (p < 0.05).ConclusionIn comorbid patients in our groups, taVNS can decrease the frequency of seizures, improve mood and quality of life, and reduce the EEG power spectrum.